Some Questions on Designing the Film Chuck in the Hole Grinding - Chen Shuxun; et al. (Jixie chuandong)
By the theory of elastic thin plateand combining closly with industrial praCtice,the thesis solves the theoretical problem ondesigning the chuck of the hole grinding, aridpresents the simple design formula which’ isvery useful to the industrial producing.